Pengangkatan Hakim Mahkamah Konstitusi (Studi Perbandingan Negara Indonesia dengan Negara Thailand) - Nasib Buha Silalahi; Muhammad Nurhidayat; Andreanysah Muhamad Hanif; Sonia Ivana Barus (Lembaga Pengembangan Kinerja Dosen, 2025)
The appointment of Constitutional Court Judges between one country and another certainly has similarities and differences. This is greatly influenced by the history, state system and political situation of a country. Therefore, a problem is formulated regarding the characteristics of the mechanism for appointing constitutional court judges between Indonesia and Thailand. This study aims to determine and analyze the differences in filling constitutional court judge positions between Indonesia and Thailand. The study uses a normative legal method using primary, secondary, and tertiary data because by using this method, this study can produce descriptive data obtained from written words related to the object of the writing. This study also uses a comparative method between Indonesia and Thailand. The results of this study indicate that there are significant differences regarding the mechanism for appointing constitutional judges. Indonesia was proposed by three state institutions with their respective procedures, then Thailand was proposed by the Judicial institution and a special committee was formed to select constitutional judges.